A Review of Recent Empirical Correlations for the Calculation of Determination of R134a's Convective Heat Transfer Coefficient in Vertical Condensers - Dalkilic, A. S.; Aktas, M.; Acikgoz, O.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Condensation heat transfer of R134a which flowed in the inner tube and cooling water which flowed in the annulus were experimentally investigated inside a smooth tube-in-tube heat exchanger in author's previous studies. In this current work, the investigational setup consists of a 0.5 m long double tube and the inner tube is made up of smooth copper tubing of 9.52 mm outer diameter and 8.1 mm inner diameter. The experiments are carried out for the mass flux range of 260-515 kg m(-2)s(-1) and the heat flux range of 11.3-55.3 kW m(-2) and also at a mean saturation temperature interval of 40-50 degrees C. The mean heat transfer coefficient of R134a is found through executing an energy equivalence predicated on the energy flow from the test section. The predictability of actual correlations in open sources proposed for two-phase annular flow are tested by using authors' experimental database. Alterations of vapor quality and saturation temperature difference with calculated condensation heat transfer coefficients are also shown according to different condensing temperatures and mass fluxes. Moreover, the independency of annular flow heat transfer empirical equations from tube orientation and the overall practicality for a vertical tube is validated. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Heat transfer coefficient; Convection; Condensation; Condenser; R134a; FLOW; TRANSITION; SMOOTH; R-134A; TUBES; Thermodynamics; Mechanics